CNS Activity of Myristica fragrans Houtt. - An Experimental Study (Bangladesh Journal of Medical Science, 2018)
Objective: To evaluatethe role of Myristica fragrans Houtt. for its analgesic, sedative and anxiogenic activity.Method: Charles Foster rats were administered orally the ethanolic extract (EEMF) and fractions of extract in ethyl acetate (EAMF), chloroform (CMF), and n-hexane (HMF). They were screened for sedative activity using Pentobarbitone sleep potentiation test, analgesic activity using Eddy’s hot plate and Tail flick test; and anxiogenic or anxiolytic activity using Open field test.Result: In pentobarbitone induced sleep potentiation test, the ethanolic extract (EEMF) and ethyl acetate fraction (EAMF) showed significant decrease in latency of sleep and highly significant increase in duration of sleep. In Open field test, EEMF, EAMF and HMF showed highly significant decrease in locomotion parameters as shown by decrease in rearing, preening and ambulation. In Eddy’s hot plate test and Tail flick test, highly significant increase in reaction time was seen in EEMF, EAMF, HMF groups.Conclusion: The observed results suggest that Myristica fragrans has analgesic, anxiogenic and sedative activity.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.98-106